Old Testament theology: fabulous dreams of the other side of time and space - Snyman, Gerrie 19XX- (Old Testament essays, 1994)
The focus in this paper falls on the process of the production of texts in other words, the process of expressing images of gods in texts. Studying the process of production entails recognition of the self, a critical awareness of the reader as well as of the author. Rhetorical criticism can be considerably constructive, since it concentrates on the human being's use of language in constructing realities.